2006
DOI: 10.1128/mcb.00534-06
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage-Induced Cell Cycle Regulation and Function of Novel Chk2 Phosphoresidues

Abstract: Chk2 kinase is activated by DNA damage to regulate cell cycle arrest, DNA repair, and apoptosis. Phosphorylation of Chk2 in vivo by ataxia telangiectasia-mutated (ATM) on threonine 68 (T68) initiates a phosphorylation cascade that promotes the full activity of Chk2. We identified three serine residues (S19, S33, and S35) on Chk2 that became phosphorylated in vivo rapidly and exclusively in response to ionizing radiation (IR)-induced DNA double-strand breaks in an ATM-and Nbs1-dependent but ataxia telangiectasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 56 publications
(67 reference statements)
2
43
0
Order By: Relevance
“…Moreover, dose-dependent experiments have shown that 5 to 10 Amol/L of VRX0466617 markedly inhibit the intracellular autophosphorylation of Chk2 on Thr 387 . Although the phosphorylation of Thr 68 by ATM is essential for Chk2 activation, two other recently identified phosphoresidues, Ser 19 and Ser 33 -35 , participate in this process (26). We have therefore examined the in vivo effect of VRX0466617 on these phosphoryl residues and showed that it inhibits, in a dose-dependence manner, the induced phosphorylation of Ser 19 seemed to be phosphorylated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dose-dependent experiments have shown that 5 to 10 Amol/L of VRX0466617 markedly inhibit the intracellular autophosphorylation of Chk2 on Thr 387 . Although the phosphorylation of Thr 68 by ATM is essential for Chk2 activation, two other recently identified phosphoresidues, Ser 19 and Ser 33 -35 , participate in this process (26). We have therefore examined the in vivo effect of VRX0466617 on these phosphoryl residues and showed that it inhibits, in a dose-dependence manner, the induced phosphorylation of Ser 19 seemed to be phosphorylated.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, activated Chk2 dissociates into a monomer and phosphorylates several key substrates, including Brca1, p53 and so on (reviewed in Ahn et al, 2004;Reinhardt and Yaffe, 2009). Recent studies have identified additional phosphorylation sites in Chk2, including Ser 19, Ser 33 and Ser 35 in the SQ/TQ region that are targeted by ATM, and Ser 516 that is autophosphorylated in cis (Mochan et al, 2003;Schwarz et al, 2003;Wu and Chen, 2003;Kurz et al, 2004;Buscemi et al, 2006). Phosphorylation at all these sites has been shown to contribute to Chk2 activation and function (Schwarz et al, 2003;Wu and Chen, 2003;Buscemi et al, 2006).…”
Section: Ddr Activation Relies Heavily On Protein Phosphorylationmentioning
confidence: 99%
“…Recent studies have identified additional phosphorylation sites in Chk2, including Ser 19, Ser 33 and Ser 35 in the SQ/TQ region that are targeted by ATM, and Ser 516 that is autophosphorylated in cis (Mochan et al, 2003;Schwarz et al, 2003;Wu and Chen, 2003;Kurz et al, 2004;Buscemi et al, 2006). Phosphorylation at all these sites has been shown to contribute to Chk2 activation and function (Schwarz et al, 2003;Wu and Chen, 2003;Buscemi et al, 2006). Similarly, DNA damage-induced Chk1 phosphorylation at Ser 317 and 345 results in kinase activation and phosphorylation of downstream targets (Zhao and Piwnica-Worms, 2001;Reinhardt and Yaffe, 2009).…”
Section: Ddr Activation Relies Heavily On Protein Phosphorylationmentioning
confidence: 99%
“…13,14 The best-characterized activating phosphorylation site of Chk2 is Thr68, 15 but phosphorylation of residues Ser19, Ser33 and Ser35 has been described to contribute to Chk2 activation. 16 The p53 pathway is strongly affected at multiple levels by DNA damage signaling. ATM, ATR, Chk1 and Chk2 were all reported to directly mediate N-terminal phosphorylation on p53.…”
mentioning
confidence: 99%